Values of Islamic Education in Ustadzah Oki Setiana Dewi Youtube Lecture - Abid Nurhuda; Nur Aini Setyaningtyas (Jurnal Pendidikan Vokasi Raflesia, 2022)
Islamic education has experienced ups and downs since ancient times along with the emergence of various kinds of challenges of the times. especially in today's era where everything is digital and technological, so most only want increased interaction, technology orientation and acceleration. Even though the true purpose of Islamic education is to give birth to complete human beings, namely faith and noble character, so that one of the steps to overcome this is by utilizing technology in spreading various positive impacts through social media. This includes spreading Islamic education through the YouTube channel, and one of the lecturers who uses this technology is Ustadzah Oki Setiana Dewi. The purpose of this study is to describe the values of Islamic education in his YouTube lecture entitled "“Ceramah Lebih Panjang Oki Setiana Dewi | Jangan Ceritakan Aib Pasangan Di Sosmed”. The method used is descriptive qualitative with data collection techniques observation and documentation then listened to, recorded and analyzed the contents to conclude. The results showed that the values of Islamic education in Ustadzah Oki Setiana Dewi's Youtube Lectures included the values of aqidah/faith related to the criteria for women who were longed for by heaven, then the values of sharia which were related to worship and mu'amalah and finally the moral values that includes morality to Allah, oneself and also others.